Liquid Desiccant-assisted Dehydration of Bio-based Oligomers - Ahmad Syafiq Ahmad Hazmi; Wan Nur Fatihah Wan Muhammad Zulkifli; Tuan Noor Maznee Tuan Ismail; Zafarizal Aldrin Azizul Hasan (Bumi Publikasi Nusantara, 2026)
We evaluate liquid desiccant–assisted coalescence to dehydrate bio-based oligomers and break water in oil emulsions under mild conditions. An experimental packed column contacted epoxidized oil with glycol in counter-current at moderate temperature and ambient pressure; moisture was measured by Karl Fischer; a thermodynamic model using cubic plus association assessed desiccant flow effects. The column operated under an apparent laminar regime to maintain film stability and encourage coalescence without disruptive turbulence. The system achieved specification moisture, and model trends agreed with experiments; laminar hydraulics promoted droplet growth and rapid gravitational separation; compared with vacuum drying, the approach delivered shorter drying duration and lower energy demand. Dehydration accelerated because glycol absorbs water, stabilizes film drainage, enlarges droplets on packing, and minimizes back mixing when flow is controlled. The approach enables continuous, economical dehydration of palm-based oligomers with simple operation, compatibility with downstream processes, and scalability for industrial production and reliability.